Assessing the Influence of Household Food Security Components on the Severity of Nutritional Status among Stunted Children in Jember Regency - Rindiani, Rindiani; Witono, Yuli; Suciati, Luh Putu; Tejasari, Tejasari (Department of Technology of Agricultural product (THP) Jambi University, 2025)
Abstract— Stunting remains a persistent public health challenge in agrarian regions, despite their high food production potential. This study examines the influence of household food security dimensions—availability, access, and utilization—on the severity of stunting among children under five in Jember Regency, Indonesia. Using a cross-sectional explanatory design, data were collected from 120 households with stunted children and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The results indicate that food access (β = –0.314, p < 0.01) and food utilization (β = –0.278, p < 0.05) have significant negative effects on stunting severity, whereas food availability does not exhibit a direct significant relationship (β = –0.128, p > 0.05). Moreover, food access mediates the effects of both availability and utilization on stunting severity, underscoring its critical role as an intermediary factor. The model accounts for 28.7% of the variance in stunting severity, affirming the multidimensional nature of food security in determining nutritional outcomes. These findings highlight the need for integrated interventions that go beyond food supply to address economic access and household nutritional practices. The study contributes to theoretical discourse by moving from a binary to a severity-based conceptualization of stunting and offers practical implications for targeted, evidence-informed nutrition policies in agrarian settings.